Complete mitochondrial genomes of the charr Salvelinus alpinus erythrinus (Salmoniformes: Salmonidae) from Arctic Canada - Alla G. Oleinik; Andrey D. Kukhlevsky; Lubov A. Skurikhina (Mitochondrial DNA Part B, 2022)
The complete mitochondrial genomes were sequenced in two individuals of charr Salvelinus alpinus erythrinus from Arctic Canada. The genome sequences were 16,652 bp in length; the genome organization and GC content (45.6%) are consistent with those of charr mitochondrial genomes published previously. The difference between the two genomes studied is low, 0.02%. Our results indicate the phylogenetic closeness of S. alpinus erythrinus and Salvelinus sp. 4 from Lake Nachikinskoe, Kamchatka and their origin from a common ancestor.